Host and Microbiome Interplay Shapes the Vaginal Microenvironment - Kwon, Myoung Seung; Lee, Heung Kyu (Frontiers in Immunology, 2022)
The female reproductive tract harbors a unique microbiome, especially the vagina. The human vaginal microbiome exhibits a low diversity and is dominated by Lactobacillus species, compared to the microbiome of other organs. The host and vaginal microbiome mutually coexist in the vaginal microenvironment. Host cells provide Lactobacillus glycogen as an energy source, and Lactobacillus produce lactic acid, which lowers vaginal pH thereby preventing growth of other bacteria. Bacterial vaginosis can modulate host immune systems, and is frequently associated with various aspects of disease, including sexually transmitted infection, gynecologic cancer, and poor pregnancy outcomes. Because of this, numerous studies focused on the impact of the vaginal microbiome on women`s health and disease. Furthermore, numerous epidemiologic studies also have demonstrated various host factors regulate the vaginal microbiome. The female reproductive tract undergoes constant fluctuations due to hormonal cycle, pregnancy, and other extrinsic factors. Depending on these fluctuations, the vaginal microbiome composition can shift temporally and dynamically. In this review, we highlight the current knowledge of how host factors modulate vaginal microbiome composition and how the vaginal microbiome contributes to maintaining homeostasis or inducing pathogenesis. A better understanding of relationship between host and vaginal microbiome could identify novel targets for diagnosis, prognosis, or treatment of microbiome-related diseases.